(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcome of acute myocardial infarction associated with a trial fibrillation. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Karachi Institute of Heart Diseases and Dow University Hospital OJHA Campus Karachi, from July 2017 to December 2017. Materials and Methods: 311 patients aged >30 years, both gender presented with acute myocardial infarction were included in the study through Outpatient department or Emergency Room. Hospital admitted patients to CCU due to acute myocardial infarction (ST elevation MI and Non ST elevation MI) were also included. Patients with severe comorbid conditions like malignancies, renal failure, COPD, or decompensated liver cirrhosis, patients already on treatment on ventricular dysfunction, AF, stroke were excluded from this study. Results: Out of 311 patients, 203(65.27%) were having STEMI, and 108(34.72%) patients were admitted with NSTEMI. Atrial Fibrillation was found in 38 (12.21%) patients. The most common clinical outcome in patients with AF was Ventricular Fibrillation, followed by Ventricular Tachycardia (VT), patients death and stroke. Among 3 patients who died, 6(15.78%) patients had VF and 4(10.52%) patient had stroke, so clinical outcome occurred in 19 out of 38 patients who developed AF. Conclusion: Rate control therapy and oral anti coagulants should be offered to patients at risk for development of atrial fibrillation, This can result in significant reduction of mortality. Key Words: Atrial fibrillation, Acute Myocardial Infarction, STEMI, NSTEMI